Farm-level benefits to investments for mitigating land degradation: empirical evidence from Ethiopia - Shiferaw, Bekele; Holden, Stein (Cambridge University Press, 2001)
Resource conservation programs have often been launched without careful evaluation of farmers' intertemporal tradeoffs in undertaking conservation investments. Such investments often have long pay back periods and reduce short-term household incomes. The critical question is whether long-term benefits would be sufficient to compensate farmers' immediate costs. Lack of empirical data on crop responses to soil erosion has hindered policy-relevant research. This study uses empirical data from the Ethiopian highlands to estimate the damage from soil erosion and evaluate the profitability of proposed conservation investments. A farm-level model is developed to study economic incentives to implement proposed conservation methods. Results show that incentives to invest in conservation practices are very low except for low cost methods like grass strips. The yield penalty due to area loss and high investment costs contribute to this. Policies focusing on minimizing the area loss effect and subsidizing the initial investment costs are shown to improve farmers' incentives to conserve the soil. A preferred policy option in the short-term is supporting low cost technologies that provide short-term benefits to poor farmers.